2021
DOI: 10.3389/fspor.2021.641389
|View full text |Cite
|
Sign up to set email alerts
|

The Training Characteristics of World-Class Male Long-Distance Cross-Country Skiers

Abstract: Purpose: To investigate the training characteristics of world-class long-distance cross-country skiers.Methods: Twelve world-class male long-distance cross-country skiing specialists reported training from their best season, through a questionnaire and follow-up interviews. Training data were systemized by training form (endurance, strength, and speed), intensity [low- (LIT), moderate- (MIT), and high-intensity training (HIT)], and exercise mode, followed by a division into different periodization phases. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…As expected from their large amounts of DP-specific training (Torvik et al, 2021 ), LDS reached higher DP-V peak in comparison with ARS during the incremental test to exhaustion with no between-group differences observed in RUN-V peak . Better DP performance in LDS was coincided by higher DP-VO 2peak , DP-VO 2peak /RUN-VO 2max ratios (i.e., 97% in LDS vs. 94% in ARS), as well as with higher GE during submaximal DP.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As expected from their large amounts of DP-specific training (Torvik et al, 2021 ), LDS reached higher DP-V peak in comparison with ARS during the incremental test to exhaustion with no between-group differences observed in RUN-V peak . Better DP performance in LDS was coincided by higher DP-VO 2peak , DP-VO 2peak /RUN-VO 2max ratios (i.e., 97% in LDS vs. 94% in ARS), as well as with higher GE during submaximal DP.…”
Section: Discussionsupporting
confidence: 67%
“…To adapt to these competitive demands, specialized long-distance XC skiers (LDSs) perform a higher percentage of their total training volume using DP than ARS (~50 vs. ~25%) (Torvik et al, 2021 ). Due to the higher volumes of DP training among LDS, superior technique-specific physiological adaptations and greater upper-body strength and power may be expected in comparison with typical ARS.…”
Section: Introductionmentioning
confidence: 99%
“…The present observation that the training intensity of our group of athletes was pyramidal in structure throughout the entire season is in accordance with other reports on the large amounts of time spent in Z1 by rowers (Steinacker et al, 1998 ; Guellich et al, 2009 ; Nybo et al, 2014 ; Plews et al, 2014 ; Treff et al, 2017 ), cyclists (Lucía et al, 2000 ; Schumacher and Mueller, 2002 ; Zapico et al, 2007 ; Neal et al, 2011 ), triathlon athletes (Neal et al, 2013 ), cross-country skiers (Torvik et al, 2021 ) and runners (Esteve-Lanao et al, 2005 ). One explanation for this finding is that low-intensity training is needed to counteract potential negative effects (e.g., autonomic and hormonal stress, energy depletion) of training at intensities at or above threshold intensity (Bourgois et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most retrospective analyses of the TID of athletes engaged in various endurance sports, such as rowing (Hartmann et al, 1990 ; Guellich et al, 2009 ; Plews et al, 2014 ), cycling (Lucía et al, 2000 ; Schumacher and Mueller, 2002 ; Zapico et al, 2007 ; Neal et al, 2011 ), swimming (Mujika et al, 1995 ; Baldassarre et al, 2019 ), running (Esteve-Lanao et al, 2005 ), triathlon (Neal et al, 2013 ) and cross-country skiing (Torvik et al, 2021 ), have revealed a pyramidal structure, with > 70% of the training being performed in Z1. However, some retrospective analyses do report utilization of a polarized TID by successful cross-country skiers (Seiler and Kjerland, 2006 ; Sandbakk et al, 2011 ; Tønnessen et al, 2014 ; Schmitt et al, 2020 ), runners (Billat et al, 2001 ) and rowers (Bourgois et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation